2018
DOI: 10.1093/aje/kwy048
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Arsenic Exposure and Arsenic Metabolism With the Metabolic Syndrome and Its Individual Components: Prospective Evidence From the Strong Heart Family Study

Abstract: Inorganic arsenic exposure is ubiquitous and both exposure and inter-individual differences in its metabolism have been associated with cardiometabolic risk. The association between arsenic exposure and arsenic metabolism with metabolic syndrome and its individual components, however, is relatively unknown. We used poisson regression with robust variance to evaluate the association between baseline arsenic exposure (urine arsenic levels) and metabolism (relative percentage of arsenic species over their sum) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 77 publications
1
48
0
Order By: Relevance
“…Arsenic methylation capacity has been related to As toxicity. In support of this, numerous observational studies have observed that a higher proportion of MMA and/or a lower proportion of DMA in urine is associated with increased risk for many adverse health effects [33], although the opposite has also been observed for certain outcomes such as diabetes and metabolic syndrome [51,52]. In the current study, when compared with non-Hispanic women, foreign-born Hispanic women had significantly higher %DMA in their urine and a corresponding trend toward lower %iAs.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Arsenic methylation capacity has been related to As toxicity. In support of this, numerous observational studies have observed that a higher proportion of MMA and/or a lower proportion of DMA in urine is associated with increased risk for many adverse health effects [33], although the opposite has also been observed for certain outcomes such as diabetes and metabolic syndrome [51,52]. In the current study, when compared with non-Hispanic women, foreign-born Hispanic women had significantly higher %DMA in their urine and a corresponding trend toward lower %iAs.…”
Section: Discussionsupporting
confidence: 73%
“…It is possible that such variants are more common in Hispanic women and may be protective against some adverse health effects of As exposure. Differences in diet or nutritional status could also play a role, as certain dietary factors (especially folate) have been related to an increased As methylation capacity [52,[56][57][58][59]. However, it is also possible that the %As metabolites do not reflect As metabolism, but rather organic arsenicals from dietary sources, in this population, as some foods, such as rice and seafood, can be sources of specific As species, such as iAs and DMA [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Also, folic acid consumption increases the biotransformation of i As leading to excretion of DMA in urine, and the reduction of MMA concentration in the blood . A more recent study pointed out that a low MMA/DMA ratio resulting from As metabolism is associated with elevated risk of overall metabolic syndrome that contribute to the risk of diabetes …”
Section: Arsenic Biotransformation and Toxicitymentioning
confidence: 99%
“…This carcinogen disrupts the bioactivity of cellular immune system causing a reduction of CD4+ cells in epidermal keratinocytes, and inducing skin carcinogenesis . Using ATO as a test compound and HaCaT keratinocytes as a test system, Udensi et al pointed out that low concentrations of arsenic modulate gene expression in the immune system. While many biomarkers such as cytokines are up‐regulated, other signaling molecules are down‐regulated.…”
Section: Mechanisms Involved In Arsenic Tumorigenesismentioning
confidence: 99%
“…Implications for human disease. In addition to its well-established role as a carcinogen, a large body of epidemiologic evidence indicates a strong association between arsenic exposure and the risk for diabetes (3,4), a conclusion supported by a comprehensive meta-analysis of the literature by the National Toxicology Program (2). However, the underlying molecular basis for this association remains unknown.…”
Section: Discussionmentioning
confidence: 99%